Developing effective research proposals - Punch, Keith F. (SAGE, 2006)
This accessible, how-to guide can be used as a workbook to the author's 'An Introduction to Social Research', or as an independent guide. It is a guide to preparing a well-constructed research proposal, then presenting it effectively